Analysis of the Relationship of Religious Character, Perseverance and Learning Motivation of Junior High School Students - Alfauzan Amin; Alimni Alimni; Dwi Agus Kurniawan; Rahmat Perdana; Wahyu Adi Pratama; Elza Triani (Journal of Innovation in Educational and Cultural Research, 2022)
The urgency of doing this research is so that educators and students have a reference on how the relationship between religion, perseverance and learning motivation in learning Islamic Religious Education. In addition, this study also aims to determine the relationship between religious attitudes and student learning persistence at SMPN 2 Bengkulu City and SMPN 2 Jambi City in the subject of Islamic Religious Education. The research design used is a quantitative research method with a correlational research design. The number of samples studied amounted to 140 students. The results showed that in the T test there was a significant comparison between variables and in the correlation test there was a significant relationship between religious attitudes, persistence and learning motivation of students at SMPN 2 Bengkulu City and SMPN 2 Jambi City on Islamic Religious Education Subjects.The implications of this research are expected to be a reference for educators and students in improving and understanding the religious character, perseverance and learning motivation of students, so that it has a good impact on the learning process, especially in Islamic religious education subjects.